Differential Effects of Alarmins on Human and Mouse Basophils - Gambardella, Adriana R.; Poto, Remo; Tirelli, Valentina; Schroeder, John T.; Marone, Gianni; Mattei, Fabrizio; Varricchi, Gilda; Schiavoni, Giovanna (Frontiers in Immunology, 2022)
Epithelial-derived alarmins (IL-33, TSLP, and IL-25) play an upstream role in the pathogenesis of asthma. Basophil-derived cytokines are a pivotal component of allergic inflammation. We evaluated the in vitro effects of IL-33, TSLP, and IL-25, alone and in combination with IL-3 on purified peripheral blood basophils (hBaso) and bone marrow-derived mouse basophils (mBaso) in modulating the production of IL-4, IL-13, CXCL8 or the mouse CXCL8 equivalents CXCL1 and CXCL2. IL-3 and IL-33, but not TSLP and IL-25, concentration-dependently induced IL-4, IL-13, and CXCL8 release from hBaso. IL-3 synergistically potentiated the release of cytokines induced by IL-33 from hBaso. In mBaso, IL-3 and IL-33 rapidly induced IL-4 and IL-13 mRNA expression and protein release. IL-33, but not IL-3, induced CXCL2 and CXCL1 from mBaso. Differently from hBaso, TSLP induced IL-4, IL-13, CXCL1 and CXCL2 mRNA expression and protein release from mBaso. IL-25 had no effect on IL-4, IL-13, and CXCL1/CXCL2 mRNA expression and protein release even in the presence of IL-3. No synergism was observed between IL-3 and either IL-25 or TSLP. IL-3 inhibited both TSLP- and IL-33-induced CXCL1 and CXCL2 release from mBaso. Our results highlight some similarities and marked differences between the effects of IL-3 and alarmins on the release of cytokines from human and mouse basophils.